Setting Sight on Role Playing: To Accommodate or to Repudiate? - Fata, Ika Apriani (Lingua Cultura, 2016)
To set sight on role play by means to look at EFL teacher’s experience and students’ perspectives of role play (RP) technique enactment in teaching speaking by using qualitative design. This research was a qualitative study. It was discharged at a Senior high school in Banda Aceh, Indonesia. It provided work for the instrument of observation sheet, field notes and interview guide, and also questionnaire. The methodology designated the combination of four mountainsides to expose in-depth the urgency of role play in which applied since 1936. The result of interview was exposed that the English teacher claimed that role play was a technique applied to promote speaking and it was corroborated by the result of field note. Likewise, regarding students’ perspective depicted that the students indeed agreed on themselves of the usefulness of role play to enhance their speaking skill and motivation. Thus, Students asserted that the learning was more fun and enjoyable through role play itself. It is merely found in this research study that role playing can accommodate students’ need and teacher’s side in English language teaching. Nevertheless, this article applies a small subject as the participant. Therefore, the researchers recommended to have a deep look at reasoning students’ point of view in terms of role play technique implementation in non-English class. And see ascertains how beneficial it is in terms of role play (RP) in a large classroom.